MEASURES TO PROMOTE TOURISM DEVELOPMENT IN THE EPIDEMIC RISKS CONDITIONS IN UKRAINE - TEODOROVYCH, LARYSA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Currently, in Ukraine there is significant change in the rate of implementation of the measures to support the tourism sector that jeopardize the competitiveness of the industry in the global market. The problems and the possible measures for tourism in Ukraine in conditions of an epidemic risks were revealed in the article. In particular, it is emphasized, now, during the stagnation of the area, the sphere of tourism in Ukraine is better than in most countries, because the international and domestic travel significantly exceed incoming flows. The tourism-related economy in Ukraine depends largely on domestic tourism, as well as the domestic component of inbound tourism. Except for the coronavirus pandemic there are a number of inhibitory factors of the development of tourism in Ukraine, including: lack of adequate support from public authorities; ineffective management and outdated legal framework; lack of proper infrastructure; illegal activity of subjects of tourist activity of the branch (in particular, activity without licenses of certificates); poor quality of road surface; pollution of recreational areas, etc. Support for the development of tourism in Ukraine at both central and local levels should be in cooperation with the specialists of the tourism business, taking into account the risks and preferences of tourists. Depending on how the world events related to the COVID-19 pandemic develop, following the recommendations developed by the UNWTO Crisis Committee, it is necessary to gradually implement the measures set out in the document "Roadmap for Competitive Tourism Development in Ukraine", as well as to implement monitoring and adapting accordingly to possible changes in world tourism. This will restart the tourism industry, reduce the negative effects of the coronary pandemic crisis, as well as create a basis for increasing the competitiveness of Ukraine in the international tourism market.